Letters from cuba eaudiobook - Behar, Ruth (Listening Library, 2020)
Pura Belpré Award Winner Ruth Behar's inspiring story of a young Jewish girl who escapes Poland to make a new life in Cuba, while she works to rescue the rest of her family The situation is getting dire for Jews in Poland on the eve of World War II. Esther's father has fled to Cuba, and she is the first one to join him. It's heartbreaking to be separated from her beloved sister, so Esther promises to write down everything that happens until they're reunited. And she does, recording both the good—the kindness of the Cuban people and her discovery of a valuable hidden talent—and the bad: the fact that Nazism has found a foothold even in Cuba. Esther's evocative letters are full of her appreciation for life and reveal a resourceful, determined girl with a rare ability to bring people together, all the while striving to get the rest of their family out of Poland before it's too late. Based on Ruth Behar's family history, this compelling story celebrates the resilience of the human spirit in the most challenging times.